Binary small molecule organic nanoparticles exhibit both direct and diffusion-limited ultrafast charge transfer with NIR excitation. Issue 5 (22nd January 2019) - Kudisch, Bryan; Maiuri, Margherita; Wang, Leon; Lim, Tristan; Lu, Hoang; Lee, Victoria; Prud'homme, Robert K.; Scholes, Gregory D.
Abstract : We report the facile synthesis on new binary organic nanoparticles composed of NIR absorbing small molecules, which we show using ultrafast spectroscopy undergo photoinduced electron transfer. Abstract : Here we describe a facile, one-step synthesis of a binary organic nanoparticle composed completely of NIR-absorbing small molecules, a quatterylene diimide and a vanadyl napthalocyanine, using Flash Nanoprecipitation. We show that the molecules are co-encapsulated within an amphiphilic block copolymer shell by observing distinct ultrafast dynamics in the binary nanoparticles compared to nanoparticles of their individual components, which we rationalize as a photoinduced charge transfer. We then draw similarities between the charge transfer dynamics studied in our system and the charge dissociation process in macroscale organic bulk heterojunction blends for OPV applications by assigning the ultrafast time component (∼10 ps) to direct interfacial charge transfer and the slow component (70–200 ps) to diffusion limited charge transfer. This discovery can inspire the development of mixed-composition nanoparticles with new functionality for optoelectronic and theranostic applications.